Blood donation motivators and barriers reported by young, first‐time whole blood donors: Examining the association of reported motivators and barriers with subsequent donation behavior and potential sex, race, and ethnic group differences. Issue 12 (24th October 2022) - France, Christopher R.; France, Janis L.; Ysidron, Dominic W.; Martin, Caroline D.; Duffy, Louisa; Kessler, Debra A.; Rebosa, Mark; Rehmani, Shiraz; Frye, Victoria; Shaz, Beth H.
Abstract: Background: A greater understanding of young, first‐time donor motivators and barriers is needed to address the ongoing challenge of retaining these essential donors. Study Design and Methods: Structured interviews conducted with 508 young, first‐time whole blood donors [66.1% female; Mean Age = 19.4 (SD = 2.5) years] were coded to identify reported motivators and barriers. Reported motivators and barriers were then examined for their association with attempted donation behavior over a 14‐month follow‐up, and for potential sex, race, and ethnic group differences in the frequency of endorsement. Results: Prosocial motivation (e.g., altruism) was the most commonly reported motivator and fear (e.g., fainting, needles) was the most commonly reported barrier. Donation behavior was unrelated to reported motivators, but was significantly related to four reported barriers including fear of fainting/dizziness, fear of needles/pain, having personal commitments that conflict with donating, and perceiving oneself as unsuited to donate for health reasons. Sex, racial, and ethnic differences were noted with respect to the percentages of donors reporting several donation‐related motivators and barriers. Conclusion: The present findings identify donation‐related barriers that could be important targets to address in the effort to encourage new young donors and to retain these new donors for the long term. Importantly, these data also highlight the importance of considering individual differences in donor motivation as a function of sex, race, and ethnicity.